Psychological Distress of Immigrant Population in Host School Systems and the Critical Period for Second Language Development: A Review. - Figueiredo, Sandra (2018)
Immigrant students attending schools in the host country have different cognitive, cultural and linguistic backgrounds that might influence their inclusion process. This process is enhanced by success attained in academic context and by psychological adaptation. Academic difficulties and limited proficiency could motivate psychological distress and anxiety levels that constraint development and learning of newer immigrants’ generation. Maladaptive behaviours might occur with different severity among non-native school children attending to their ethnic differences, cultural traits, length of residence and age. Also the maturational characteristics that interfere with the achievement of native children are probably different from the cognitive maturation that explain the performance of immigrant students, in the same schooling years. In this critical review two main concerns are explored as research based evidence and also as theoretical hypotheses: how distinct immigrant groups differ in psychological distress according to pre-migration and post-migration experiences, and how immigration may change the cognitive processing abilities and the brain development.